Port Management Integration in Government Strategy to Address the Impact of the United States’ Reciprocal Tariff Policy on National Export Competitiveness - Kusumawati, Evyana Diah; Karmanis; Karjono (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2025)
The reciprocal tariff policy implemented by the United States toward its trading partners, including Indonesia, has exerted significant pressure on the competitiveness of Indonesia’s exports. Key sectors such as textiles, agriculture, and light manufacturing have been among the most affected. In this context, logistics efficiency, particularly port management as a strategic node in the export supply chain play a pivotal role. This study aims to analyze the impact of such tariff policies on Indonesia’s export performance, identify structural challenges in port management, and formulate strategies for integrating port governance into national policy frameworks to enhance export competitiveness. Employing a qualitative approach, this research utilizes data collection techniques including document analysis and in-depth interviews with stakeholders in the port, logistics, and trade sectors. The findings indicate that tariff barriers undermine export competitiveness, and inefficiencies in the port system driven by poor inter-agency coordination, infrastructural disparities, and fragmented logistics policies emerge as critical constraints. The study underscores the importance of an adaptive, collaborative, and nationally coordinated port management strategy to bolster Indonesia’s response to the growing pressures of global protectionism. It highlights the urgent need for comprehensive reform in port governance to strengthen Indonesia’s position in the international export market.